(3QSGdI aj GdefWbs ((3Ydi Hf LeGd GdOjf GdJQcSJGfi s)
(3ChdgG (B:s
(3hGdBOGH LeY COH hGdeQGO bGd hgj eQJHg Ydi KdGKI aUhd s
(3BNQgG (B:s
(3hEf de jcf KGHJkG jdRe CjVkG HYV Tehd GdYOe hCeG eG cGf jdRe gPG BNQ eG ChQOfG ai TQM gPg hGdMeO ddg ChdkG hBNQkG hGdUdGI Ydi QShdg eMeO hBdg hCUMGHg CLeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdeLGejYs